Violation of labour rights and social security rights: The problems in practice and the need for revision - Stevanović Aleksandar (University of Belgrade - Faculty of Law, Belgrade & Institute of Comparative Law, Belgrade, 2021)
The aim of the paper is to determine the main characteristics of the crime in question. It was pointed out that this is a criminal norm that provides protection to labor relations in a general way, i.e. workers' rights. Therefore, there are numerous ambiguities in judicial practice, mostly concerning the legal qualification of the violation of labor regulations and issues of proper application of the ne bis in idem principle. The paper specifically points to de lege ferenda legal solutions that would aim to more clearly determine the scope of labor rights that are protected by the relevant criminal norm.